Coronavirus Disease (Covid-19), is Global Recession Evitable? - Bilkisu Maijamaa; N. O Nweze; Hauwa Daniyan Bagudu (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2020)
COVID-19 (Coronavirus Disease-2019) is regarded as a public health emergency of international concern. Patients contracting the severe form of the disease constitute approximately 15% of the cases [WHO). The covid-19 is affecting 203 countries and territories around the world. An epidemiological threat such as COVID-19 can have destructive effect on the economy.it is of great importance not to focus only on the epidemiological profile of the virus but also its impact on the economy. As much as economists think about risk-taking as a key driver of the economy, an economy only works if risks are largely known. With the impact of the covid-19 on travel services, durable expenditure, on supply chain and on social isolation (high skilled working from home, home schooling) and impact on demand and supply. On the bases of the listed impact on the economy global recession seems inevitable, there is also possibility of emerging markets. The overall demand effect is probably higher than the initial supply shock. There will be uncertainties, panic, a lot of panic buying and lock-down policies is a key to drive large drop in demand. The investment in a lot of firms especially the small and young firms, spending for households such as rent and mortgagor’s depend largely on cash flow. Large drop in demand will lead to force closure in a lot of firms and this will lead to an increase in lay-offs and hence further drop in consumption, and sadly the economy leads to depressing loop.